THE TAXONOMY OF EDUCATIONAL OBJECTIVES: AN EVALUATION OF THE LEARNING DOMAINS - Aliyu, Iya Gana; Ismail, Yusuf; Liman, Mukhtar Alhaji (Sokoto Educational Review, 2015)
The role of the taxonomy of education in the formal educational system cannot be over-emphasized; as such, the paper examines the concept of learning domains which include: cognitive domain, affective domain and psychomotor domain in curriculum contents delivery. The role of teachers in the utilization and actualization of the three learning domains in teaching and learning which involves proper and effective selection of the appropriate keywords (verbs) for the statement of behavioral objectives, choice of the past learning experiences of learners and the effective usage of instructional media for the attainment of instructional objectives of a lesson in which many teachers' more especially prospective teachers' faced with these challenges. The authors also suggest that for effective teaching and learning to prevail in any formal educational system , teachers being the implementers of schools ' curriculum should imbibe and enact the taxonomy of educational objectives in teaching and learning encounter for a better achievement of instructional objectives by embracing the following strategies such as: teachers' mastery of their subject-matter, effective utilization of learners past experiences and proper selection, appropriateness and usage of instructional media, all of which could be attained through attending of educational programs like short-courses, refresher workshops, symposiums, seminars and conferences.